Reductions of topologically massive gravity I: Hamiltonian analysis of second order degenerate Lagrangians - Ucgun, Filiz Cagatay; Esen, Ogul; Gumral, Hasan (Amer Inst Physics, 2018)
We present Skinner-Rusk and Hamiltonian formalisms of second order degenerate Clement and Sarioglu-Tekin Lagrangians. The Dirac-Bergmann constraint algorithm is employed to obtain Hamiltonian realizations of Lagrangian theories. The Gotay-Nester-Hinds algorithm is used to investigate Skinner-Rusk formalisms of these systems. Published by AIP Publishing.
Keywords: Dirac-Bergmann Theory; Systems; Formulation; Formalism; Ostrogradski; Equations; Dynamics; Models